A polymorph bactericidal defect and a lupus-like syndrome. Issue 5 (May 1981) - Levinsky, R J; Harvey, B A; Roberton, D M; Wolff, O H
Abstract : We describe a child with primary defect of polymorph bacterial killing associated with systemic lungs erythematosus. We suggest that her autoimmune disease results from chronic bacterial antigen stimulation and propose a hypothetical model linking immunodeficiency with autoimmunity.